Looking toward Lake Washington over Geyser Basin showing the Manufactures Building and the Music Pavilion, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
Printed on image: Looking toward Lake Washington over Geyser Basin, Alaska Yukon Pacific Exposition, 1909, Seattle, Wash. Official post card. Printed on verso: Portland Post Card Co. PH Coll 777 PPCC.120 (See also PH Coll 433.21) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number